FtsH Protease in the Thylakoid Membrane: Physiological Functions and the Regulation of Protease Activity - Kato, Yusuke; Sakamoto, Wataru (Frontiers in Plant Science, 2018)
Protein homeostasis in the thylakoid membranes is dependent on protein quality control mechanisms, which are necessary to remove photodamaged and misfolded proteins. An ATP-dependent zinc metalloprotease, FtsH, is the major thylakoid membrane protease. FtsH proteases in the thylakoid membranes of Arabidopsis thaliana form a hetero-hexameric complex consisting of four FtsH subunits, which are divided into two types: type A (FtsH1 and FtsH5) and type B (FtsH2 and FtsH8). An increasing number of studies have identified the critical roles of FtsH in the biogenesis of thylakoid membranes and quality control in the photosystem II repair cycle. Furthermore, the involvement of FtsH proteolysis in a singlet oxygen- and EXECUTER1-dependent retrograde signaling mechanism has been suggested recently. FtsH is also involved in the degradation and assembly of several protein complexes in the photosynthetic electron-transport pathways. In this minireview, we provide an update on the functions of FtsH in thylakoid biogenesis and describe our current understanding of the D1 degradation processes in the photosystem II repair cycle. We also discuss the regulation mechanisms of FtsH protease activity, which suggest the flexible oligomerization capability of FtsH in the chloroplasts of seed plants.